Islamic Education Curriculum Reform as a Pathway to Muslim Nationalism in Germany - Firma, Heldi; Helmiati; Muhammad Nazir (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This paper examines how the reform of the Islamic education curriculum in Germany serves as an effort to strengthen Muslim nationalism within the context of a pluralistic and secular German society. Using a qualitative descriptive method through a literature study, this research analyzes curriculum policies. The findings show that curriculum reform includes integrating inclusive Islamic teachings, national values, and interfaith dialogue into the Islamic education curriculum. These reform efforts contribute significantly to the development of Muslim nationalism in Germany. The implications of Islamic Religious Education in Germany include improved learning outcomes and significant changes in the teaching and learning system in schools. These reforms also call for changes in the legal framework to ensure and regulate the implementation of a nationally consistent Islamic Religious Education system in the country.